Large databases in economic history : research methods and case studies - Casson, Mark, 1945-; Hashimzade, Nigar (Abingdon, Oxon : Routledge, 2013)
"'Big data' is now readily available to economic historians, thanks to the digitisation of primary sources, collaborative research linking different data sets, and the publication of databases on the internet. Key economic indicators, such as the consumer price index, can be tracked over long periods, and qualitative information, such as land use, can be converted to a quantitative form. In order to fully exploit these innovations it is necessary to use sophisticated statistical techniques to reveal the patterns hidden in datasets, and this book shows how this can be done.A distinguished group of economic historians have teamed up with younger researchers to pilot the application of new techniques to 'big data'. Topics addressed in this volume include prices and the standard of living, money supply, credit markets, land values and land use, transport, technological innovation, and business networks. The research spans the medieval, early modern and modern periods. Research methods include simultaneous equation systems, stochastic trends and discrete choice modelling.This book is essential reading for doctoral and post-doctoral researchers in business, economic and social history. The case studies will also appeal to historical geographers and applied econometricians"--
1. Introduction : research methods for large databases / Mark Casson and Nigar Hashimzade -- 2. Long-run price dynamics : the measurement of substitutability between commodities / Mark Casson, Nigar Hashimzade and Catherine Casson -- 3. The quantity theory of money in historical perspective / Nick Mayhew -- 4. Medieval foreign exchange : a time series analysis / Adrian R. Bell, Chris Brooks and Tony K. Moore -- 5. Local property values in fourteenth- and fifteenth-century England / Margaret Yates, Anna Campbell and Mark Casson -- 6. Visual analytics for large-scale actor networks : a case study of Liverpool, 1750-1810 / John Haggerty and Sheryllynne Haggerty -- 7. Railways and local population growth : Northamptonshire and Rutland, 1801-91 / Mark Casson. [et al.] -- 8. Women's landownership in England in the nineteenth century / Janet Casson -- 9. The diffusion of steam technology in England : ploughing engines, 1859-1930 / Jane McCutchan -- 10. Cupidity and crime : consumption as revealed by insights from the Old Bailey records of thefts in the eighteenth and nineteenth centuries / Sara Horrell, Jane Humphries and Ken Sneath.
Keywords: Economic indicators -- Statistical methods; Big data -- Statistical methods